ANALISIS YURIDIS PENYELESAIAN KREDIT BERMASALAH ATAS JAMINAN GADAI DALAM PRAKTEK DI PEGADAIAN STUDI PADA PT. PEGADAIAN PERSERO CABANG RANTAUPRAPAT - Muhammad Rudini Harahap; Hasim Purba; Megarita Megarita; Idha Aprilyana Sembiring (Universitas Sumatera Utara, 2018)
ABSTRACT The results of the study indicate that problem loans in PT. Pegadaian (persero) Branch Rantauprapat in the last five years (2012-2016) the are fifty cases caused by the following factors, first because of the unstable price of oil palm commodity which is the main source of local revenue Labuhanbatu, secondly because the business owned by the customer suffered a loss, third because there is no good faith from customers to pay off debt, and the last causal factor of the customer abusing the credit provided. The sale of the object of the mortgage guarantee is by the parate eksekusi by the pawnshop, associated with the rules Otoritas Jasa Keuangan (OJK) number 31/POJK.05/2016 about the pawnshop effort under article 24 paragrafh (3) the sale of the pledge security object can be done in to ways : the customer sells his or her own guarantee object of authorizes the pawnshop to make a sale against the pledge object. Sale against the object of the morgage guarantee that can not cover the debt, then the customer is responsible for the remaining debt. If the customer can not pay off the remaining debt, the impact received by the customer in the next stage of the customer can not make a loan if a time requires funds because the customer’s identity has been on the black list. The black list can last two years or more. Keywords : Nonperforming Loan, Mortgage Guarantees